Beyond Autonomy Fetishism: Affiliation with Autonomy in Women's Empowerment. Issue 1 (2nd January 2016) - Khader, Serene
Abstract: A growing critical literature on women's empowerment argues that the current focus on autonomy obscures the extent to which relationships, social norms, and structures shape women's lives. I begin from the idea that disaggregating forms of autonomy and conceptually clarifying their relationship to empowerment can help us respond to the critiques without abandoning what is genuinely important about autonomy. I argue that one form of personal autonomy, thin relational autonomy, is necessary but insufficient for women's empowerment. Seeing this can help us respond to the critiques as well as develop a better understanding of what should be prioritized in development interventions. In order to agitate against oppressive structures and to improve their lives in ways they endorse, women need the ability to formulate and scrutinize their own values. This conception of autonomy, unlike many other conceptions of autonomy, does not exclude the idea that relationships can be empowering. However, this conception of autonomy is also not sufficient for empowerment; empowerment also requires non-autonomy goods and changes in conditions external to the agent.